Unveiling the Environmental and Economic Implications of Additive Manufacturing on Inbound Transportation - Fischer, Leon; Schmitz, Emma Becker (Journal of Sustainable Manufacturing in Transportation, 2024)
This study aims to investigate the impact of additive manufacturing (AM) on the sustainability of inbound transportation. By combining insights from existing literature and interviews with professionals in the additive manufacturing field, we present a comprehensive analysis of this subject. Drawing upon both literature review and interview perspectives, it is evident that AM significantly influences the sustainable dimension of transportation. A key attribute of additive manufacturing is its inherent efficiency, resulting in minimized waste generation during production. This stands in contrast to traditional manufacturing methods, which involve material reduction to achieve desired shapes. The streamlined process of additive manufacturing requires fewer raw materials, thereby reducing environmental impact. The transportability of filament powder in bulk form further contributes to these sustainability gains, reducing material volume and transportation frequency. Consequently, emissions associated with additive manufacturing-related transportation are lowered. Recycling of materials is also structured within a broader framework, deviating from the conventional model of product returns to manufacturers. Despite its potential, our empirical findings suggest that the adoption of additive manufacturing doesn't consistently lead to cost reduction compared to conventional methods. The applicability of additive manufacturing remains limited to specific product ranges. Nevertheless, cost savings can occur in the realm of inbound transportation due to factors such as reduced transportation frequency and the transport-friendly nature of raw material containers. Furthermore, the efficiency of raw material usage in additive manufacturing contributes to economic benefits. Unlike conventional manufacturing, additive processes don't require extensive raw material inventories. Economic considerations extend to the adoption of distributed manufacturing systems. While centralized systems minimize raw material transportation, they may increase transportation distance for the final products. Conversely, distributed systems increase raw material travel but decrease product transportation distance. The study underscores that while distributed manufacturing offers advantages, it impacts transportation costs. In essence, this study sheds light on the complex interplay between additive manufacturing and inbound transportation sustainability. It underscores how additive manufacturing's inherent efficiencies and material characteristics have ramifications for environmental and economic dimensions. Through a blend of theoretical insights and empirical evidence, this research contributes to the broader discourse on sustainable manufacturing practices.